PERFORMANCE ACCOUNTABILITY OF GOVERNMENT AGENCIES IN WAJO DISTRICT SOUTH SULAWESI - Syamsu Alam; Tenriwaru Tenriwaru; Andi Nurwanah (Universitas Islam Balitar, 2016)
This study aims to determine how the competence of the financial apparatus and the application of the financial accounting system in realizing the qualitative characteristics of regional financial statements so it can become a reflection of the achievement of the performance accountability of local government agencies as regional financial managers. The data of the research is primary quantitative data obtained directly from the source or place where the research was conducted. The data collection conducted a survey using a questionnaire instrument which was measured using a Likert scale. The data analysis method used was the Descriptive Statistical Test and Partial Least Square (PLS) by performing the Outer Model Test - Measurement Model and Inner Model Test - Structural Model. The findings of this study are: 1) Apparatus competence has a significant effect on the quality of regional financial statements; 2) The regional financial accounting system has a significant effect on the quality of regional financial statements; 3) Apparatus competence has a significant effect on the performance accountability of government agencies: 4) The regional financial accounting system has a significant effect on the accountability of the performance of government agencies; 5) The quality of regional financial statement has a significant effect on the performance accountability of government agencies; 6) Apparatus competence has a significant effect on the performance accountability of government agencies through the preparation of quality regional financial statements; 7) The regional financial accounting system has a significant effect on the performance accountability of government agencies through the preparation of quality regional financial statements.